Rifampicin and Isoniazid Maximal Concentrations are Below Efficacy-associated Thresholds in the Majority of Patients: Time to Increase the Doses? - Trentalange, Alice; Borgogno, Enrica; Motta, Ilaria; Antonucci, Miriam; Pirriatore, Veronica; Costa, Cecilia; Rossi, Giovanni; Barco, Ambra; De Nicolò, Amedeo; Piccioni, Pavilio; D'Avolio, Antonio; Bonora, Stefano; et al. (International journal of antimicrobial agents, 2021)
•The majority of participants showed low rifampin and isoniazid plasmatic maximal concentrations at two early time points.•Ca. one-fifth of patients had suboptimal exposure to two or more drugs.•Higher doses/kg, being born in Italy, female gender, proton pump inhibitor use, and older age were among the variables that influenced plasmatic drug concentrations.•Increasing doses as well as the use of therapeutic drug monitoring in certain patient groups may be advised. The treatment of drug-sensitive tuberculosis (TB) is highly effective; however, many patients have suboptimal drug exposure, which possibly explains treatment failures and selection of resistance. This study aimed to describe the prevalence and determinants of suboptimal maximal concentrations (Cmax) for anti-TB drugs. An observational study was conducted in patients receiving first-line anti-TB treatment. At two early time points (T1 and T2), blood samples were withdrawn 2 hours post-dose (Cmax) and drug concentrations were measured. Data were expressed as medians (interquartile ranges). The study included 199 participants: 72.9% were male and the median age was 39.8 years (27.5–51.4). The median Cmax at T1 and T2 were 7950 ng/mL and 7122 ng/mL (rifampicin), 3260 ng/mL and 3185 ng/mL (isoniazid), 4210 ng/mL and 5742 ng/mL (ethambutol), and 31 008 ng/mL and 30 352 ng/mL (pyrazinamide), respectively. Higher doses/kg and other variables (being born in Italy and female gender for rifampicin, older age and proton pump inhibitor use for isoniazid, female gender and older age for pyrazinamide) were identified by multivariate linear regression analysis. Participants with a higher body mass index received lower doses/kg of all anti-TB drugs. Suboptimal Cmax at T1 and T2 were observed in 60% and 66% (rifampicin), 54% and 55% (isoniazid), 33% and 39% (ethambutol), 20% and 11% (pyrazinamide) of patients. Despite 21% of patients at T1 and 24% at T2 showing two or more drugs with suboptimal exposure, no effect on treatment outcome was observed. The majority of patients receiving first-line anti-TB drugs had low isoniazid and rifampin Cmax. Increased doses or the use of therapeutic drug monitoring in selected patients may be advised.